INTERFERENSI BAHASA MELAYU TERNATE DALAM PROSES PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VIII SMP NASIONAL BANAU KOTA TERNATE - Rio Sukarno; Rafik M. Abasa (Universitas Khairun, 2021)
This research aims to explain the occurrence of Ternate's Malay interference in the process of learning Indonesian VIII grade students at Banau National Middle School in Ternate City describing the factors causing interference in the learning process of Ternate Malay language class VIII Banau National Middle School, Ternate City. This study used descriptive qualitative method. The data used are primary data and secondary data. Data sources were 28 students who spoke Malay in Ternate. Data collection techniques are observation (observation), interview (Interview), decommentation, Speaking. Data analysis techniques use descriptive qualitative (data reduction, data presentation, passing conclusions and verification). Based on data analysis, it was concluded that the Malay language of Ternate in the process of learning Indonesian language in class VIII of Banau National Middle School in Ternate City was found, namely; (a) interference in the form of words, sentences, phrases, and clauses. (b) interference occurs, namely the occurrence of the learning process of Indonesian language in grade VIII Banau National Middle School in Ternate City, namely; (1) Habits, (2) Affected by others (3) preferred or comfortable using Malay language Ternate (4) have not realized or accustomed to using Indonesian in the learning process (5) friends use Ternate Malay language. Causes of Ternate Malay Language Interference, namely; (1) habits, (2) the interlocutors (3) are more comfortable using the Malay language of Ternate (4) have not mastered the Indonesian language (formal).